Implementation of Digitalization and Work Effectiveness on Reducing Human Error Rate in Store Send Indonesia - Hafida, Hafida; Ridho, Muhammad Rasyid; Ananda, Billy Budi; Sihombing, Sarinah (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
The condition of logistical activity that is currently ongoing in the warehouse of Cakung PT. Store Send Indonesia still needs improvement, especially in the storage process, because there are still some problems, such as goods returned from customers because of the wrong goods, goods Less, Goods More, and Inappropriate goods caused by Human Error. This research aims to analyze the implementation of digitalization and the effectiveness of work in reducing the level of human error in the operational warehouse of PT. Store Send Indonesia. The study involved 82 respondents from PT. Store Send Indonesia employees as a population and sample, using saturated sampling techniques. The research method used is a double linear regression analysis to determine the impact of digitization implementation and work efficiency on the level of human error. In addition, validity tests are also carried out to ensure that the data obtained is valid. The results show that digitalization does not significantly reduce human error; work effectiveness significantly reduces human error, and digitalization and work effectiveness simultaneously reduce human error in the PT Store Send Indonesia warehouse.